The Effect Of Butterfly Pea Flower Tea On Brain Weight In Wistar Rats After D-Galactose Induction - Budiastuti, Ernadita; Pratama, Yanasta Yudo; Pramaningtyas, Miranti Dewi; Adnan, Muhammad Luthfi (Universitas Muhammadiyah Malang, 2024)
Introduction: Butterfly pea flowers (Clitoria ternatea L.) currently popular in society as high-antioxidant supplement. One of the organs affected by aging is the brain. D-galactose is a compound that is widely used for induction of aging in animal studies. The aim of this study was to assess the effect of butterfly pea flower tea on changes in brain weight in mice induced by D-galactose. Method: 24 rats were divided into four groups consisting of control, groups with 1%, 5%, and 10% butterfly pea flower tea intervention after being induced by aging for 6 weeks. The brain organs were then weighed to assess changes in each group. Result: There was an increase in body weight but no significant differences between each group either before or after the intervention. No significant differences were found in the average brain weight of each group, with the brain weight of the P3 group being lower than that of the other intervention groups. There is a positive correlation between body weight and brain weight. Conclusion: Although the butterfly pea flower has no statistically significant effect, at concentrations of 1% and 10% it can have an effect on brain weight after induction of aging by D-galactose.